Mechanical properties and antibiotic release characteristics of poly(methyl methacrylate)-based bone cement formulated with mesoporous silica nanoparticles. (August 2017) - Letchmanan, Kumaran; Shen, Shou-Cang; Ng, Wai Kiong; Kingshuk, Poddar; Shi, Zhilong; Wang, Wilson; Tan, Reginald B.H.
Abstract: The influence of mesoporous silica nanoparticles (MSNs) loaded with antibiotics on the mechanical properties of functional poly(methyl methacrylate)-(PMMA) based bone cements is investigated. The incorporation of MSNs to the bone cements (8.15 wt%) shows no detrimental effects on the biomechanical properties of the freshly solidified bone cements. Importantly, there are no significant changes in the compression strength and bending modulus up to 6 months of aging in PBS buffer solution. The preserved mechanical properties of MSN-functionalized bone cements is attributed to the unchanged microstructures of the cements, as more than 96% of MSNs remains in the bone cement matrix to support the cement structures after 6 months of aging. In addition, the MSN-functionalized bone cements are able to increase the drug release of gentamicin (GTMC) significantly as compared with commercially available antibiotic-loaded bone cements. It can be attributed to the loaded nano-sized MSNs with uniform pore channels which build up an effective nano-network path enable the diffusion and extended release of GTMC. The combination of excellent mechanical properties and sustainable drug delivery efficiency demonstrates the potential applicability of MSN-functionalized PMMA bone cements for orthopedic surgery to prevent post-surgery infection. Graphical abstract: Highlights: MSN-functionalized bone cements enable efficient and sustained delivery of GTMC. MSNs afforded an effective nano-sized diffusion network in the bone cements. Loaded MSNs shows no effects on the biomechanical properties of the bone cements. More than 96% of MSNs remains in the matrix to support the cement structures. MSN-functionalized cements exhibited sustainable antibacterial activity.